Adverse Events Associated With ClariFix Posterior Nasal Nerve Cryoablation: A MAUDE Database Analysis. (2nd February 2021) - Singh, Amrita K.; Kasle, David A.; Torabi, Sina J.; Manes, R. Peter
Abstract : Posterior nasal nerve (PNN) cryoablation is a novel surgical technique used to address chronic rhinitis. The purpose of this study is to review the medical device reports (MDRs) submitted to the Food and Drug Administration's (FDA) Manufacturer and User Device Facility Experience (MAUDE) database to identify adverse events related to the use of ClariFix, a device designed for office‐based cryosurgical ablation of the PNN. A total of 12 adverse events associated with ClariFix from January 2017 to August 2020 were identified and analyzed. The most common adverse events associated with ClariFix PNN cryoablation include epistaxis and nasal swelling. Further studies are needed to clarify whether PNN cryoablation is associated with epistaxis in certain populations.